Customer Experience (CX) for Optimizing Human-Centered Design in Education and Training Program Services at BKPSDM Pandeglang Regency - Handoko, Pryo; Kurnia, Nina; Solihin, Ihin; Tania, Reni (Jurnal Manajemen Pelayanan Publik, 2024)
This study aims to explore how the integration of Customer Experience (CX) and Human-Centered Design (HCD) principles can optimize education and training services at BKPSDM Pandeglang Regency. The research adopts a qualitative approach to investigate participant experiences and identify key factors that influence satisfaction, engagement, and service effectiveness. Data were collected from 15 informants through in-depth interviews, document analysis, and observations, followed by thematic analysis to extract key themes. The findings highlight significant challenges in communication, access to facilities, and innovation in learning methodologies, while also showcasing the positive impact of modern teaching techniques and active participant involvement on satisfaction levels. Unique insights reveal that ineffective communication and evaluations perceived as formalities undermine participant trust, despite otherwise satisfactory service delivery. The study underscores the importance of integrating user-centered innovations and responsive communication channels to create services that not only meet procedural standards but also inspire and motivate. This research contributes to theoretical discussions on CX and HCD in public services and offers practical recommendations for developing adaptive, participant-focused programs. Future studies are encouraged to empirically validate the proposed model in broader public service contexts.